Aplikasi E-Commerce Sebagai Jembatan Perancang dan Konsumen Pada T-Shirt Design - Hendry Hendry; Teddy Marcus Zakaria (Jurnal Teknik Informatika dan Sistem Informasi, 2017)
Abstract — In Indonesia, there is still not a special website that accommodates designers to design, to sell t-shirts with their own design, most websites only sell t-shirts. Abroad, some websites have been selling design t-shirts such as Teespring.  Teespring makes it easy to create, sell, and order custom t-shirts, but  has  the  disadvantage  that  the price is  less  affordable for the people of Indonesia.  T-Shirt Design is  an e-commerce  website  that makes it easy to create, sell and order custom t-shirts with affordable prices. T-Shirt Design embraces  designers  as  sellers with  their  own design  products  and  accomodate selling their custom t-shirts. T-Shirt Design will process orders from designer/seller and display t-shirt products that have ready to sell to consumer. Consumer can order, buy t-shirt product, and pay it.  After receiving the product, consumer will give the feedback that use to improve serving, accuration, expedition. Designer/Seller get selling report, inventory report and list of consumer for each shop. Keywords—Custom T-Shirt, E-commerce,  T-Shirt Design